IMMUNOSTIMULATORY EFFECT OF FATTY ACID FROM STAR FISH (ACANTHASTER PLANCI) ON LYMPHOCYTE PROLIFERATION IN-VITRO - M. Janib Achmad; Alim Isnansetyo; Noer Kasanah; Ustadi Ustadi; Kamiso Kamiso (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2014)
The aims of this study were to investigate lymphocyte proliferation activity and to identify chemical constituents of active fractions of star fish Acanthaster planci. A. planci was collected from Ternate Island, North Moluccas, extracted with distilled methanol and water, partitioned with gradient chloroform-hexane-methanol-water and fractionated in column chromatography using silica gel and hexane-ethyl acetate-methanol. The active compound had been purified by Thin Layer Chromatography (TLC) and identified by Gas Chromatography-Mass Spectrometry (GC-MS). The lymphocyte proliferation activity was measured based on % Stimulation Index (SI) from sample absorbency and control absorbency. The result showed that the 3 fractions of hexane fraction exhibited lymphocyte proliferation activity. Fraction 1 was able to increase lymphocyte proliferation at 48 hours and 72 hours by 55% (80 µl/ml) and 88% (160 µl/ml) increase, and fraction 2 had 77% (160 µl/ml) and 86% (640 µl/ml) increase. Meanwhile, fraction 3 had 75% (640 µl/ml) and 89% (640 µl/ml) increase. Metabolite analysis of active fraction using GC-MS yielded a number of chemical constituents that was dominated by fatty acid. The study concluded that star fish A. planci from Ternate Island has a potential source of immunostimulator.